Communication In Sampyong Arts In Majalengka - Rina Indriani; Dadang Iskandar; Arifin Ahmad (Jurnal Mamangan, 2023)
This article aims to explore the communication that occurred in Sampyong art performance originating from Majalengka Regency of West Java Province. The research method used is literature study and observation. This form of communication from Sampyong art can be seen from the performance to the end of the show, where there is a process of verbal and non-verbal communication in its implementation which involves not only players, but also spectators and the public. Communication is certainly involving many parties, including players, gamelan players, malandang, audience, and the community. This can certainly illustrate the importance of communication as one of support in community life and collaborating with others in any case, of course by realizing that we are social beings who definitely need others